Respuesta :

Answer:

(i) a = 2

   b = -1

   c = -1

(ii) x= 1

Step-by-step explanation:

Step 1: Factorise

[tex]f(x) = 2(x^{2} -2x+\frac{1}{2})[/tex]  

Step 2: Use the complete square method.

[tex]f(x)=2(x^{2} -2x+(\frac{-2}{2})^{2} + \frac{1}{2} - (\frac{-2}{2})^{2} )[/tex]  

Step 3: Have it to [tex]a(x+b)^{2} +c[/tex]

[tex]f(x)=2((x-1)^{2} -\frac{1}{2} )\\ = 2(x-1)^{2} -1[/tex]

Line of symmetry:  

To find line of symmetry, we use -b/2a formula.

Based from [tex]2x^{2} -4x+1[/tex]:

a=2, b=-4

-b/2a = -(-4)/2(2) = 1